62 Patient Experience with Clinical Trials: Results from the International Kidney Cancer Coalition Global Patient Survey - Eric Jonasch; Stênio de Cássio Zequi; Axel Bex; Deborah Maskens; Margaret Hickey; Karin Kastrati; Christine Collins; Michael Jewett (The Oncologist, 2026)
Abstract Background Clinical trials are essential for advancing cancer care, yet patient participation remains suboptimal worldwide. While structural and clinician-reported barriers are well described, patient perspectives across diverse geographic and socioeconomic settings are less understood. The International Kidney Cancer Coalition (IKCC) conducts a biennial Global Patient Survey (GPS) to assess patient and caregiver experiences with kidney cancer, including clinical trials, to identify unmet needs and inform global advocacy. Methods The 2025 IKCC GPS was developed by a steering committee comprising patient advocates, medical experts, and the Picker Institute. The target population was kidney cancer patients, with responses provided directly by patients or caregivers reporting on their behalf. The survey was cognitively tested, translated into 16 languages, and distributed globally via online and paper formats. Data were analyzed using descriptive statistics and cross-tabulations. Results A total of 2,677 respondents (patients, n = 2,049; caregivers, n = 628) from 46 countries participated, including 551 from low- and middle-income countries (LMICs) and 2,126 from high-income countries (HICs). Respondents were predominantly male (54%), aged 46–80 years (80%), with clear cell histology (62%); 19% presented with stage IV disease, and 52% were diagnosed within the past four years. Globally, 64% reported willingness to participate in a clinical trial if offered; willingness was significantly higher in HICs than LMICs (69% vs. 46%, p < 0.001). Only 30% reported being asked to participate, with HIC respondents asked more often than those in LMICs (30% vs. 23%, p < 0.001). Among those asked, 83% agreed and 63% ultimately enrolled — rates comparable between HICs and LMICs. The leading drivers of participation were physician recommendation (64%), perceived access to better treatments (53%), and desire to contribute to KC research (48%). Overall trial satisfaction was 77%, with no significant difference between HICs and LMICs. Qualitative feedback (n = 333) identified perceived clinical benefit as the dominant satisfaction driver (63%), followed by close monitoring and specialized care (45–54%), access to new treatments (50%), psychological reassurance (29%), and altruism (18%). Dissatisfaction was most commonly attributed to treatment-related factors, including toxicity (58%) and lack of efficacy or limited duration of benefit (46%). System-level issues were also prominent: communication gaps — such as insufficient explanation of side effects and lack of feedback on trial results — were reported by 34%; operational challenges, including enrollment delays and lack of coordination by 28%; and logistical burdens such as travel and frequent visits by 25%. Additionally, 22% described emotional distress related to uncertainty or unmet expectations, and 18% perceived limited patient-centeredness, including rigid protocols or insufficient individualized care. Conclusions While willingness to participate in clinical trials is high, opportunities remain critically limited — fewer than one in three patients were offered participation, with even lower rates in LMICs. When offered, acceptance and enrollment rates are substantial. Although overall satisfaction is high, patient experience is meaningfully undermined by toxicity, limited efficacy, and systemic care delivery challenges. These findings highlight the urgent need to integrate routine clinical trial discussions into standard oncology care, expand equitable global access, and prioritize patient-centered trial design and delivery.